2015
DOI: 10.1042/bj20141066
|View full text |Cite
|
Sign up to set email alerts
|

The MAP kinase-interacting kinases regulate cell migration, vimentin expression and eIF4E/CYFIP1 binding

Abstract: The MAP kinase-interacting kinases (Mnk1 and Mnk2) are activated by ERK and are best known for phosphorylating the translation initiation factor eIF4E. Genetic knockout of the Mnks impaired the migration of embryonic fibroblasts both in two-dimensional wound-healing experiments and in three-dimensional migration assays. Furthermore, a novel and selective Mnk inhibitor, Mnk-I1, which potently blocks eIF4E phosphorylation, blocked the migration of fibroblasts and cancer cells, without exerting 'off-target' effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 53 publications
3
62
0
Order By: Relevance
“…Their catalytic domains share 78% sequence identity and the active sites are highly conserved [25,57]. MNK1 and MNK2 display the canonical bilobal arrangement of the ATP-binding cleft sandwiched in between the C-terminal and N-terminal lobes.…”
Section: Mapk-interacting Kinasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Their catalytic domains share 78% sequence identity and the active sites are highly conserved [25,57]. MNK1 and MNK2 display the canonical bilobal arrangement of the ATP-binding cleft sandwiched in between the C-terminal and N-terminal lobes.…”
Section: Mapk-interacting Kinasesmentioning
confidence: 99%
“…Recent studies have found that high levels of eIF4E-P coincided with poor clinical outcome in human cancers [22][23][24]. MNK1 and MNK2 are serine/threonine protein kinases responsible for the phosphorylation of S209 on eIF4E [25]. The phosphorylation of eIF4E correlates with the increase in mesenchymal markers such as N-cadherin, fibronectin and vimentin, along with the acquisition of invasive properties [26].…”
Section: Dual Targeting Of Mnks Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Beside its structural role, vimentin is also involved with cellular migration and signal transduction [56]. Vimentin interacts with several kinases such as protein kinase A, protein kinase C, calcium calmodulin kinase, p21-activated kinase, Cdc2 kinase, Rho-kinase, Aurora-B polo-like kinase, Akt kinase, and Mnk1/2 which phosphorylate one or more of 41 sites on vimentin identified to date [57][58][59]. Higher expression of vimentin has been observed in cancer cells and correlates with induction of epithelial-to-mesenchymal transition, metastasis, and poor cancer prognosis.…”
Section: Cytoskeletal Organizing and Structural Proteinsmentioning
confidence: 98%